Petőfi Sándor és a hiteles kép - Bódi, Katalin (Studia Litteraria, 2024)
The history of Sándor Petőfi’s visual representations can be examined with the concept of the true image of Hans Belting which makes a connection between faith and picture: the existence of Christ is confirmed by portraits for Christian worshipers and pictures have their devotional function for Christian communities. There are many portraits and genre paintings made during Petőfi’s life, but thanks to his cult there were many pictures painted of him even after his death. It is known to posterity that his portrait was recorded in a daguerreotype in the 1840s, but its status in his cult is still uncertain, because it was only found in 1868 in the legacy of her wife Júlia Szendrey, meaning that his depictions right after his death were based above all on the painting tradition and the personal practice of remembrance. In the 1870’s, after the presentation of the daguerreotype to the larger public, there was a debate in the press about the true image of Petőfi, which shows a rivalry between artistic and technical portraits. In my paper, I review the changing relationship between Petőfi’s pictorial representations and the concept of the true image in the 19th and early 20th centuries.